"Religious commitment and its relationship to reducing psychological stress in breast cancer patients" (Comprehensive Journal of Science, 2024)
This research aimed to investigate the relationship between religious commitment and psychological stress among breast cancer patients, using a descriptive correlational approach. The sample consisted of 20 patients. The Religious Commitment Scale (prepared by Ziad Barakat, 2006) and the Psychological Stress Scale (developed by the researcher) were administered. The results showed that the highest percentage of the sample (40%) fell within the 37–42 age group, followed by the 31–36 age group (35%), and then the 25–30 age group (25%). The mean age was 34.65 years with a standard deviation of 5.60, indicating a normal distribution. The results also revealed a statistically significant inverse correlation between religious commitment and psychological stress; that is, the higher the level of religious commitment, the lower the level of psychological stress among breast cancer patients. The results indicated that the level of religious commitment among the sample ranged from moderate to high, while the levels of psychological stress varied. The results confirm that religious commitment is an important factor in improving psychological adjustment and reducing psychological stress among breast cancer patients, through the spiritual and moral support it provides that helps in coping with the disease.
Keywords: Religious commitment, psychological stress, breast cancer patients.